An Observing System Simulation Experiment for Ocean State Estimation to Assess the Performance of the SWOT Mission: Part 1—A Twin Experiment. Issue 7 (13th July 2019) - Li, Zhijin; Wang, Jinbo; Fu, Lee‐Lueng
Abstract: The Surface Water Ocean Topography (SWOT) satellite mission is planned for launch in 2021. It will use the technique of radar interferometry to measure sea surface height over a 120‐km‐wide swath with a 20‐km gap around the satellite's nadir track. The oceanographic objectives of the mission are to study ocean circulation at scales down to 15 km. To prepare for the evaluation of the mission's performance, we are undertaking a series of studies to explore the efficacy of an assimilative high‐resolution modeling system for estimating the state of the ocean based on independent observations from both spaceborne and in situ measurements. The system is based on the heritage of a multiscale approach to data assimilation by the Regional Ocean Modeling System. Observing System Simulation Experiments were first conducted in the setup of an identical twin experiment to assess the system's performance near the calibration/validation site of SWOT off the coast of California. The system was applied to a nested model domain with 1‐km resolution. Simulated satellite observations of SSH, sea surface temperature, salinity, in situ observations of upper ocean temperature, and salinity by profiling floats and a dedicated notional array of station‐keeping gliders were assimilated by the system. The results indicate that such an observing system can accurately estimate the state of the ocean, and in particular SSH for the evaluation of SWOT performance. Key Points: A multiscale modeling and data assimilation system has been developed for the SWOT mission The data assimilation system is used to conduct Observing System Simulation Experiments (OSSEs) for SWOT calibration and validation It is shown that an observing system with an array of 20 station‐keeping gliders can reconstruct accurate SSH estimates for SWOT calibration and validation